Peles braiadas: modos de ser Kalankó - Herbetta, Alexandre Ferraz (2011)
The Kalankó community lives in the hinterland of Alagoas, more specifically in the municipality of Água Branca/AL. They have reinforced their indigenous identity publicly since the end of the 1990s, receiving the official classification by the federal government as Indians - in 2003. The field of ethnology classifies this phenomenon as ethnogenesis, among other related terms. These studies focus on the relationship between these populations and the nation state. This thesis aims to understand the Kalankó point of view as to what it means to be a Kalankó person. It is also a study on the symbolic system that is based on native music that acts as the pivot of a complex ritual that connects the mythology with some cultural domains and points out a complex representation of reality. In this sense, this thesis also attempts to understand how this representation is used to establish similarities and differences of strategic importance to the other peoples of the region and Brazil. In addition, I seek to understand what is an indigenous identity from the indigenous perspective. As a consequence, this provides insight into what is human. This thesis is based on a series of eight trips to the region, divided asymmetrically among indigenous groups in the same area, as well as major urban centers of the region, with the main focus on Kalankó villages. In this sense, one of the objectives of this thesis is to carry out studies on the concept of culture and identity, contributing to the field of anthropology. And beyond that, it tries to reposition Kalankó and other indigenous peoples of the northeastern hinterlands among ethnology in Brazil, leaving them symmetrically among other indigenous people, expanding the possibilities of the understanding of human phenomenon